ChemInform Abstract: Silica Gel‐Promoted Convenient Synthesis of 2‐Bromo‐3‐hydroxybenzoate Derivatives. Issue 10 (March 2015) - Shinohara, Hiroyuki; Sonoda, Motohiro; Hayagane, Naoya; Kita, Shota; Tanimori, Shinji; Ogawa, Akiya
Abstract The product formation in the presence of FeCl3 is accompanied by generation of a regioisomer which can be troublesome to separate.